Management and economics of communication - Rimscha, Bjørn von, 1978- (Handbooks of communication science, 2020)
This handbook combines the perspectives of communication studies, economics and management, and psychology in order to provide a comprehensive economic view on personal and mass communication.It is divided into six parts that comprise: 1. an overarching introduction that defines the field and provides a brief overview of its history (1 chapter)2. the most commonly used theoretic frameworks for the analysis of communication economics and management (4 chapters)3. the peculiarities of the quantitative and qualitative methods and data used in the field (3 chapters)4. key issues of the field such as the economics of language, labor in creative industries, media concentration, branding etc. (10 chapters)5. descriptions of the development, trends and peculiarities of the field in different parts of the world, written by scholars from the respective region (10 chapters)6. reflections on future directions for the field, both from a managerial and from an economics perspective (1 chapter). The authors of the individual chapters represent different academic disciplines, research traditions, and geographic backgrounds. The reader will thus gain multifaceted insights into the management and economics of communication.